2016
DOI: 10.1536/ihj.15-493
|View full text |Cite
|
Sign up to set email alerts
|

A Single Session of Neuromuscular Electrical Stimulation Enhances Vascular Endothelial Function and Peripheral Blood Circulation in Patients With Acute Myocardial Infarction

Abstract: SummaryThis study aimed to investigate whether a single session of neuromuscular electrical stimulation (NMES) can enhance vascular endothelial function and peripheral blood circulation in patients with acute myocardial infarction (AMI). Thirty-four male patients with AMI were alternately assigned to 2 groups, and received NMES with muscle contraction (NMES group, n = 17) or without muscle contraction (control group, n = 17) after admission. NMES was performed for quadriceps and gastrocnemius muscles of both l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…35,36 In contrast, several studies have suggested changes in autonomic activity and cardiovascular response when subjects performed RT or NMES alone. 18,19,37 This study did not show that adding NMES to RT elicited a worse response to autonomic activity or cardiovascular response compared to RT alone. The results from this study support the safety of RT þ NMES, as shown in the results of previous studies investigating RT or NMES alone from the aspect of evaluating autonomic activity and cardiovascular response.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…35,36 In contrast, several studies have suggested changes in autonomic activity and cardiovascular response when subjects performed RT or NMES alone. 18,19,37 This study did not show that adding NMES to RT elicited a worse response to autonomic activity or cardiovascular response compared to RT alone. The results from this study support the safety of RT þ NMES, as shown in the results of previous studies investigating RT or NMES alone from the aspect of evaluating autonomic activity and cardiovascular response.…”
Section: Discussioncontrasting
confidence: 57%
“…18 On the other hand, NMES was reported to slightly but signi¯cantly increase the blood pressure and sympathetic activity in patients with acute myocardial infarction. 19 However, few studies have reported on autonomic activity and cardiovascular responses during RT þ NMES, including reports on healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…13) Although the low-frequency component of blood pressure variability, an indicator of cardiac sympathetic nerve activity, was increased during NMES, heart rate did not significantly change and the elevation of systolic and diastolic blood pressure was within 10 mmHg. Neither arrhythmia, ischemic ST-T change, nor chest pain was induced by NMES.…”
Section: Article P676mentioning
confidence: 87%
“…Although many issues remain to be solved, the report by Tanaka, et al first showed the safety of NMES in AMI patients, 13) providing with us an initial step towards further investigations on the various effects of NMES in patients suffering from AMI. …”
Section: Article P676mentioning
confidence: 99%
“…Inflammation and oxidative stress are strongly associated with the progression of endothelial dysfunction; in turn, the latter is the physiopathological substrate of several cardiovascular diseases with high impact on mortality indices such as myocardial infarction, cerebrovascular disease, and chronic renal failure [ 33 , 34 , 35 ]. Thus, treatments to control both conditions are emerging as key therapies against these high-impact diseases [ 1 ].…”
Section: Discussionmentioning
confidence: 99%